Electronic cigarette use among US adults in the Population Assessment of Tobacco and Health (PATH) Study, 2013–2014. Issue Volume 26:Issue e2(2017) (17th June 2017) - Coleman, Blair N; Rostron, Brian; Johnson, Sarah E; Ambrose, Bridget K; Pearson, Jennifer; Stanton, Cassandra A; Wang, Baoguang; Delnevo, Cristine; Bansal-Travers, Maansi; Kimmel, Heather L; Goniewicz, Maciej L; Niaura, Raymond; et al.
Abstract : Background: Electronic cigarette (e-cigarette) use in the USA is increasing. As such, it is critical to understand who uses e-cigarettes, how e-cigarettes are used and what types of products are prevalent. This study assesses patterns of current e-cigarette use among daily and non-daily adult users in the 2013–2014 Population Assessment of Tobacco and Health (PATH) Study. Methods: We examined the proportion of current adult e-cigarette users (n=3642) reporting infrequent use (use on 'some days' and use on 0–2 of the past 30 days), moderate use (use on 'some days' and use on >2 of the past 30 days) and daily use. We examined demographic characteristics, use of other tobacco products and e-cigarette product characteristics overall and by use category. Adjusted prevalence ratios (aPRs) were calculated using Poisson regression to assess correlates of daily e-cigarette use. Results: Among the 5.5% of adult current e-cigarette users in the PATH Study, 42.2% reported infrequent use, 36.5% reported moderate use and 21.3% reported daily use. Cigarette smokers who quit in the past year were more likely to report daily e-cigarette use, compared with current smokers (aPR=3.21, 95% CI=2.75 to 3.76). Those who reported using rechargeable or refillable devices were more likely to report daily use compared with those who did not use these devices (aPR=1.95, 95% CI=1.44 to 2.65 and aPR=2.10, 95% CI=1.75 to 2.52, respectively). Conclusions: The majority of e-cigarette users in this study reported less than daily use. Compared with non-daily use, daily use was associated with being a former smoker; however, cross-sectional data limits our ability to establish the temporality or directionality of such associations.